Multi-Scenario Simulation of Land Use Change Along with Ecosystem Service Value for the Lanzhou–Xining Urban Agglomeration - Jing Bai; Zhuo Jia; Yufan Sun; Chengyi Zheng; Mingxing Wen (Land)
Research on the characteristics of land use change in urban agglomerations and its influences on ecosystem service value has important theoretical significance and practical value for supporting spatial development and guaranteeing ecological security. Located in the upper reaches of China’s Yellow River, the Lanzhou–Xining urban agglomeration is situated in the mosaic of the transition from the Qinghai–Tibet Plateau to the Loess Plateau. It is a substantial industrial base and economic region of western China. It is also the essence of a relatively concentrated population and dense cities. It is not only a key development area but also an essential ecological barrier in western China, shouldering the important responsibility of ensuring a win-win situation for both economic and social development and ecological and environmental protection. This research takes the Lanzhou–Xining urban agglomeration as a case region, investigates the characteristics of changes in land use and ecosystem service value from 2000 to 2020, and applies the PLUS model to emulate land use changes and ecosystem service value in 2030 in three scenarios: the natural development scenario, cultivated land protection scenario, and ecological conservation scenario. The results indicate that: (1) The land use type of the Lanzhou–Xining urban agglomeration from 2000 to 2020 was dominated by grassland, accounting for 60.32~61.25% of the gross area. The reciprocal transfer between cultivated land and grassland was the most significant, and the expansion of construction land mainly took over cultivated land and grassland, accounting for 58.23% and 34.84%. (2) As a result of ecological rehabilitation projects and the continuous increase of water areas, the ecosystem service value of Lanzhou–Xining urban agglomeration continued to increase between 2000 and 2020, with a cumulative total of 56.84 × 108 yuan and a growth rate of 2.67%. Grassland donated the most to the ecosystem service value, constituting 52.56~53.44%. Among the individual ecosystem service values, hydrological regulation and climate regulation contributed the most, and together accounted for 50.86~51.69% of the ecosystem service value. (3) Under the natural development scenario, unrestricted urban sprawl has taken possession of cultivated land and grassland. Under the cultivated land protection scenario, cultivated land has maintained a relatively stable level while construction has been subject to certain constraints. Under the ecological conservation scenario, ecological land has been largely protected and the encroachment of construction onto ecological land has been curbed. (4) Of the three scenarios, only the ecological conservation scenario saw an increase in the ecosystem service values compared to 2020. The reduction in grassland and water area was the main cause for the decrease of the ecosystem service values in the natural development scenario and cultivated land protection scenario. The results can supply a solid foundation for decision-making for future development of the Lanzhou–Xining urban agglomeration and the rational use of land, as well as offer references for the ecological conservation and high-quality development of urban agglomerations in the upper reaches of the Yellow River.